2008
DOI: 10.1194/jlr.m800168-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

siRNA screening reveals JNK2 as an evolutionary conserved regulator of triglyceride homeostasis

Abstract: Lipid homeostasis is essential for proper function of cells and organisms. To unravel new regulators of this system, we developed a screening procedure, combining RNA interference in HeLa cells and TLC, which enabled us to monitor modifications of lipid composition resulting from short, interfering RNA knock-downs. We applied this technique to the analysis of 600 human kinases. Despite the occurrence of off-target effects, we identified JNK2 as a new player in triglyceride (TG) homeostasis and lipid droplet me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…Lipids were recovered by a two‐step methanol/chloroform extraction as described (53). Settings that ensure accurate and robust quantification have been established in our previous work regarding sample amount, extraction procedure and mass spectrometric measurements (34,53,54). Basically, 900 000 cells (harvested following 4, 24 and 48 h of incubation) were taken up in 180 μL of 155 m m ammonia carbonate and 100 pmol of each lipid standard was added (PE‐O 20:0/‐O 20:0; PC‐O 18:0/‐O18:0; SM 35:1; Cer 35:1; GlcCer 30:1) and then extracted with 900 μL chloroform/methanol (10:1), while the water phase was further extracted with chloroform/methanol (2:1).…”
Section: Methodsmentioning
confidence: 99%
“…Lipids were recovered by a two‐step methanol/chloroform extraction as described (53). Settings that ensure accurate and robust quantification have been established in our previous work regarding sample amount, extraction procedure and mass spectrometric measurements (34,53,54). Basically, 900 000 cells (harvested following 4, 24 and 48 h of incubation) were taken up in 180 μL of 155 m m ammonia carbonate and 100 pmol of each lipid standard was added (PE‐O 20:0/‐O 20:0; PC‐O 18:0/‐O18:0; SM 35:1; Cer 35:1; GlcCer 30:1) and then extracted with 900 μL chloroform/methanol (10:1), while the water phase was further extracted with chloroform/methanol (2:1).…”
Section: Methodsmentioning
confidence: 99%
“…This is of special concern when performing screens with mammalian cells, given the high number of genes with multiple paralogs and the complexity of the mammalian lipidome. In an attempt to perform a large‐scale screening of protein kinases involved in lipid homeostasis in mammalian cells, Grimard and others [47] perform a siRNA knockdown of 600 human kinases combined with TLC analysis of lipids. Despite the limitations of the approach in terms of sensitivity of lipid profiling, the screen yielded 91 hits with a lipid phenotype, eventually characterizing JNK2 as a new regulator of triglyceride homeostasis.…”
Section: Lipids Homeostasis and Function – Studies And Different Apprmentioning
confidence: 99%
“…Small interfering RNA (siRNA) screening revealed that JNK2 is a regulator of LD homeostasis in HeLa cells ( 33 ). Furthermore, we recently showed that JNK2 is required for insulin-induced LD formation in human adipocytes ( 23 ).…”
Section: Methodsmentioning
confidence: 99%